2010
DOI: 10.1038/nphoton.2010.166
|View full text |Cite
|
Sign up to set email alerts
|

Optical pacing of the embryonic heart

Abstract: Light has been used to noninvasively alter the excitability of both neural and cardiac tissue 1–10. Recently, pulsed laser light has been shown to be capable of eliciting action potentials in peripheral nerves and in cultured cardiomyocytes 7–10. Here, we demonstrate for the first time optical pacing (OP) of an intact heart in vivo. Pulsed 1.875 μm infrared laser light was employed to lock the heart rate to the pulse frequency of the laser. A laser Doppler velocimetry (LDV) signal was used to verify the pacing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
137
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(148 citation statements)
references
References 20 publications
4
137
0
Order By: Relevance
“…This study explored the effects of temperature changes on membrane capacitance and its associated currents in a joint attempt to clarify the experimental results of a key recent study [16] and to pave the way towards predictive modeling of INS [2][3][4][5][6][7][8][9][10][11][12][13][14][15] and other thermal neurostimulation techniques [18][19][20], which could potentially facilitate the development of more advanced and multimodal methods for neural circuit control. Another key motivation to pursue this problem came from our noting the very similar temperature-related capacitance rates of change observed in very different model systems [ Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study explored the effects of temperature changes on membrane capacitance and its associated currents in a joint attempt to clarify the experimental results of a key recent study [16] and to pave the way towards predictive modeling of INS [2][3][4][5][6][7][8][9][10][11][12][13][14][15] and other thermal neurostimulation techniques [18][19][20], which could potentially facilitate the development of more advanced and multimodal methods for neural circuit control. Another key motivation to pursue this problem came from our noting the very similar temperature-related capacitance rates of change observed in very different model systems [ Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Both approaches also offer the long-term prospect of remotely affecting aberrant localized neural circuits that underlie many neurological diseases. A multitude of INS-related studies explored the ability of short-wave infrared (IR) pulses to stimulate neural structures including peripheral [3,4] and cranial nerves [5][6][7][8][9][10], retinal and cortical neurons [10][11][12], as well as cardiomyocytes [13,14]. It is stipulated that the INS phenomenon is mediated by temperature transients induced by IR absorption [15][16][17]; such transients can alternatively be induced using other forms of photoabsorption [18][19][20], or potentially by any other physical form of thermal neurostimulation that can be driven rapidly enough [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Likewise, ∼1.8 μm IR pulse exposure has also been demonstrated to block action potential (AP) generation and propagation. [9][10][11][12][13] While a rapid increase in temperature, due to absorption of the laser radiation, is required to evoke the neural depolarization, and IR stimulation pulses have been shown to produce an acoustic pressure wave, 14-17 the mechanism(s) to stimulate or inhibit an AP is not fully understood.…”
mentioning
confidence: 99%
“…This wavelength was selected based on results of previous studies in cardiomyocytes and neurons. [27][28][29]31 …”
Section: Ir Stimulationmentioning
confidence: 99%
“…30 Multiple groups have reported that pulsed IR evokes intracellular Ca 2+ responses and contraction in cardiomyocytes, which match the time course of the IR stimuli delivered. 28,29,31,32 In the present study, the IR-evoked contraction of NCSC-CM cardiospheres was monitored. Furthermore, we studied whether the derived cells continue to respond to long periods of IR stimulation and whether such stimulation may cause any irreversible damage to the NCSC-CMs.…”
mentioning
confidence: 99%